Emotional suppression among primary school students (Journal of the College of Basic Education, 2026)
The study aimed to identify emotional reticence among primary school students, and to reveal the significance of differences in emotional reticence according to the variable (gender). The study sample consisted of 100 male and female students from Baghdad Al-Rusafa First Schools, and the emotional reticence scale was adopted (Taylor, 1992). Data were collected and processed statistically, and the results confirmed that primary school students suffer from high levels of emotional reticence and that there are no statistically significant differences between males and females on the emotional reticence scale.